Electrospun sorbents for solid phase extraction (SPE) and colorimetric detection of pesticides - Gulamussen, Noor Jehan (Rhodes University, Faculty of Science, Department of Chemistry, 2014)
The thesis presents the evaluation of polysulfone sorbents for solid phase extraction (SPE) and the development of colorimetric probes for pesticides analysis in water. Through electrospraying and electrospinning techniques, different morphologies of sorbents (particles, beaded fibers and bead-free fibers) were fabricated. The sorbents were morphologically characterized by scanning electron microscopy. Adsorption capacities of sorbents were evaluated by conducting recoveries studies for model pesticides; atrazine, chlorpyrifos and DDT using batch and column SPE modes. Better recovery results were achieved by employing the batch mode of fibers, as values ranged from 98 to 105percent. Further sorbent evaluation was conducted using breakthrough experiments and static experiments. The breakthrough studies indicated that 1700 Î¼L was the sample volume that could be percolated with no breakthrough of the analyte that correspond to a concentration of 150 mg/g of sorbent that can be extracted without any loss of analyte. From static studies, quantities of each model compound adsorbed into the fiber at the equilibrium time were evaluated. The adsorbed atrazine was 65, chlorpyrifos 250 and DDT 400 mg/g of sorbent. Kinetic studies suggested retention mechanism following pseudo first and second order model observed by high correlation coefficients (> 0. 96), demonstrating the fiber affinity to retain both polar and non-polar compounds opening a possibility to be used as sorbent for sample preparation of different classes of pesticides in water. For the second part of the study simple strategies for colorimetric sensing based on silver nanoparticles and polivinylpyrrolidone capped nanoparticles were developed, respectively for atrazine and chlorpyrifos detection. The limits of detection of the methods were 3.32 and 0.88 mg/L for atrazine and chlorpyrifos respectively. The applicability of the probe in real samples was demonstrated by the recoveries studies of tap water varying from 94 to 104 percent. The versatility of the probe was demonstrated by affording a simple, rapid and selective detection of atrazine and chlorpyrifos in the presence of other pesticides by direct analysis without employing any sample handling steps. Attempt to incorporate the probes in a solid support was achieved by using nylon 6 as solid support polymer proving to be fast and useful for on-site detection.
Keywords: Sorbents; Electrospinning; Extraction (Chemistry); Colorimetry; Pesticides; Water -- Pesticide content -- Research